Radiographic Outcomes in Treatment of Thumb Basal Joint Arthritis: Does Interposition of Acellular Dermal Allograft Prevent Metacarpal Settling? - Khurana, Sonya; Chen, Kevin K.; Brooks, Jeffrey J. (Journal of Hand and Microsurgery, 2019)
Background Osteoarthritis at the thumb carpometacarpal joint can have a profound impact on quality of life. Here, we evaluate radiographic outcomes in patients who have had open complete trapeziectomy, ligament reconstruction with tendon interposition, and acellular dermal matrix (GraftJacket) interposition—Group A, and compare them with those without GraftJacket interposition—Group B.Materials and Methods Thirty patients who had undergone operative treatment for thumb basal joint arthritis by a single surgeon from 2009 to 2016 were identified, and charts were retrospectively reviewed for demographic data, surgical and radiographic outcomes, and complications.Results There was no significant difference in pre- and postoperative radial abduction or pre- and postoperative palmar abduction. The difference in intraoperative joint space was significant (p = 0.006), but the difference in postoperative joint space was not (p = 0.310). The average amount of metacarpal settling was 6.9 versus 3.7 mm (p = 0.035) (Groups A and B, respectively). Three patients in Group A developed an inflammatory reaction to the GraftJacket, and one required reoperation for allograft removal.Conclusion This study suggests that thumb basal joint arthroplasty with GraftJacket interposition does not lead to more favorable radiographic outcomes at long-term follow-up. The increased costs associated with GraftJacket use may not be justified in light of these outcomes.
Keywords: trapeziectomy; interposition arthroplasty; thumb carpometacarpal arthritis